Oxidized LDL Receptor 1 gene polymorphism in patients with Metabolic Syndrome. (7th November 2012) - Palmieri, Vincenzo O.; Coppola, Brigida; Grattagliano, Ignazio; Casieri, Valentina; Cardinale, Giovanna; Portincasa, Piero; Palasciano, Giuseppe; Di Serio, Francesca
<x xml:space="preserve">Abstract</x> Eur J Clin Invest 2012 Abstract Aims The lectin‐like oxidized low‐density lipoprotein receptor‐1 (LOX‐1), encoded by the OLR1 gene, has been implicated in the pathogenesis of atherosclerosis. We therefore evaluated the genotyping of OLR1 gene in a sample of 55 patients with Metabolic Syndrome, a clinical condition characterized by a high cardiovascular risk. Methods and Patients The genotyping of the LOX‐1 was performed by polymerase chain reaction (PCR) analysis of the IVS4‐14 A>G OLR1 polymorphism embedded within the OLR1 Linkage Disequilibrium block. Patients were assessed for routine serum parameters, microalbuminuria, insulin resistance (HOMA) and oxidative stress (thiobarbituric acid reactive substances, TBARs and thioredoxin). Results The allele or genotype distribution of the OLR1 IVS4‐14 A>G was not statistically different between MS and controls subjects. A positive association was found between IVS4‐14 GG genotype, microalbuminuria and fasting glycaemia as well as a higher frequency of type 2 diabetes, elevated microalbuminuria, fasting serum glucose and HOMA index in the same subjects. Thioredoxin values were higher in patients with MS but did not differ in relation to OLR1 IVS4‐14 A>G genotype. The TBARs/Cholesterol ratio was higher in MS both in IVS4‐14 GG and in IVS4‐14 AG. Conclusion IVS4‐14 GG genotype seems to be related to glucose metabolism disturbance, elevated insulin level and lipid peroxidation in patients with MS.